Occupational exposure to HIV among healthcare workers in PMTCT sites in Port Harcourt, Nigeria - Ndubuisi Akpuh; IkeOluwapo Ajayi; Ayo Adebowale; Hadejia Idris Suleiman; Patrick Nguku; Mahmood Dalhat; Elizabeth Adedire (BMC, 2020)
Abstract Background Rivers State is among the states with high HIV prevalence in Nigeria. Occupational exposure to HIV through blood or body fluids of HIV/AIDS patients is a recognised risk factor of HIV infections among healthcare workers. We identified the determinants of occupational exposures to HIV among healthcare workers in Prevention of Maternal to Child Transmission (PMTCT) sites within Port Harcourt metropolis in Rivers State. Methods A descriptive cross-sectional study was conducted and multi-stage sampling technique was used to select 341 healthcare providers from 22 public and 22 private health facilities in PMTCT sites in Port Harcourt metropolis. The data collected were analysed using descriptive statistics, Chi-square and logistic regression models (p-value = 0.05). Results Respondents' mean age was 35.9 ± SD8.4 years, 270 (80.1%) and 171(50.7%) were females, and from public health facilities respectively. Prevalence of occupational exposure of healthcare workers to HIV in the past 12 months was 153 (45.0%), and 96 (63.3%) experienced such exposure more than once. Contacts with potentially infectious body fluid accounted for the largest proportion 51 (33.3%); followed by needle stick prick 49 (32.6%). About 189 (56.1%) had safety information at their disposal and this serves as a reminder on safety precautions. The likelihood of occupational exposure was significantly higher among doctors (AOR = 2.22, 95% C.I = 1.16-4.25,) but lower among environmental health workers (AOR = 0.10, 95% C.I = 0.02-0.46,) than nurses/midwives when other factors were included in the model. Conclusion Occupational exposure to blood and body fluids remains a frequent occurrence among healthcare workers; highest among doctors in PMTCT sites in the study area. Provision of protective safety materials, training and enforcement of adherence to universal precaution strategies are highly recommended.